Spinsters in jeopardy - Marsh, Ngaio, 1895-1982 (Marsh, Ngaio, 1895-1982. Alleyn mysteries., 2014)
"Inspector Alleyn has decamped for the South of France for a vacation en famille. Well, the famille will be vay-caying while Alleyn does a little official poking around. Unfortunately, the object of his poking--the cultish denizens of a sinister and luxurious chateau--are not over-fond of being poked, and they have a particularly unpleasant way of getting their point across."--Back cover.